UPCAT passers why they opted not to study at UPV - Ang, Tiffany; Barba, Louraine Gay; Bayot, Rheanne; Gesulgon, Jill
The study is all about the factors that influenced the decision of UPCAT passers who opted not to study at UPV specifically the socio-economic and demographic factors. The respondents of the study are selected students who took and passed the UPCAT however opted not to study at UPV. These students are from Central Philippine University (CPU), West Visayas State University (WVSU), Western Institute of Technology (WIT), Iloilo Doctor's College (IDC), Siliman University, University of Saint La Salle (USLS), and fellowship Baptist College (FBC).